Changes in the vat rates in ukraine and their comparison with other european countries - Khoma, A. R. (NAU, 2021)
Taxation is the most popular topic of accounting. Taxes accompany any enterprise or institution throughout its existence. When buying and selling goods, materials, works, services and other non-current assets, VAT is present. However, it is not included in the cost of goods and materials and immediately goes to the state. Why does it exist, what percentage is its rate, how does it affect the country's economy and just what is VAT? – All these questions can be answered. But to understand its effectiveness as a tax, it is necessary to compare it with the taxes of countries where the tax system is better established and is the main source of budget enrichment.
Keywords: taxation; taxes; VAT; import; agricultural products; a value-added taxf